FACTORS INFLUENCING DEVELOPMENT LEVEL OF SETTLEMENTS IN SOUTHTRANSDANUBIA - Tamás MOLNÁR (Journal of Central European Agriculture, 2007)
Study delivers an overview on general approach of economic development being most commonly connected to GDP per capita values The given index, however – beside its advantages – shows up a number of disadvantages e.g. it can be calculated only on county- (NUTS III) level. A regional statistical classifi cation system has already been created in Hungary but on the compulsory NUTS II level (regions) the development levels of counties, micro-regions and settlements are remarkably different. Development level is measured on settlement level by the author on the basis of 17 socio-economic and infrastructural factors. Results point out that differences between the development level of settlements failed to decrease, in contrary the gaps slightly increased by the end of the examined period as it is shown by the variation co-effi cient of annually calculated Complex Development Index.